The habitat and dietary preferences of Dark-bellied Brent Geese and Wigeon in relation to agricultural management - Williams, Gwyn; Forbes, Janet E (Wildfowl, 1980)
The habitat and dietary preferences of Dark-bellied Brent Geese Branta b. bernicla and Wigeon Anas penelope on Chetney Marshes, Kent, were established and related to the agricultural management of the peninsula. Faeces were collected from several areas of Chetney and analysed. The habitats of the area were surveyed and the sward composition of three main grassland types identified. Faecal and sward composition were compared and the grazing preferences for the various habitats established. The study showed that in the Chetney area, Brent Geese and Wigeon preferred to feed in intertidal habitats. Approximately two-thirds of usage was in marine environments. When feeding on land both Brent Geese and Wigeon showed a preference for fertilized, slurry-treated grassland. The Brent Goose showed a greater tendency for feeding on arable land than did Wigeon. The feeding distribution of Wigeon, however, was modified by their intolerance of disturbance.